2016
DOI: 10.4103/1995-705x.192559
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for the outcome of aortic regurgitation after cardiac surgery in patients with ventricular septal defect and aortic cusp prolapse in Saudi patients

Abstract: Background and Aim:Aortic valve (AV) prolapse and subsequent aortic regurgitation (AR) are two complications of ventricular septal defects (VSD) that are located close to or in direct contact with the AV. This finding is one of the indications for surgical VSD closure even in the absence of symptoms to protect the AV integrity. The goal of our study was to assess the outcome and to identify the predictors for improvement or progression of AR after surgical repair.Materials and Methods:A retrospective study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
1
7
0
1
Order By: Relevance
“…Albeit, Salih et al showed female gender a risk factor for later progression of disease. 20 Comparing our results to local studies, Kumari et al 4 showed 84% regression of aortic valve disease after surgical repair. They showed 57% of residual VSD which reduced to 30% after one year follow Tariq Waqar et al up.…”
Section: Repair Of Aortic Valve Prolapse and Regurgitation In Vsdsupporting
confidence: 70%
See 1 more Smart Citation
“…Albeit, Salih et al showed female gender a risk factor for later progression of disease. 20 Comparing our results to local studies, Kumari et al 4 showed 84% regression of aortic valve disease after surgical repair. They showed 57% of residual VSD which reduced to 30% after one year follow Tariq Waqar et al up.…”
Section: Repair Of Aortic Valve Prolapse and Regurgitation In Vsdsupporting
confidence: 70%
“…Albeit, Salih et al showed female gender a risk factor for later progression of disease. 20 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, subarterial VSD requires close monitoring from the moment of diagnosis, and early surgical closure of subarterial VSD is strongly recommended once aortic valve deformity is present and even before the onset of aortic valve deformity, as preoperative AR or aortic valve prolapse are the risk factors of postoperative residual AR or AR progression [2, 46, 8]. However, given that there is no definite time for elective closure of subarterial VSD, some pediatric cardiologists still delay the surgical closure and wait until an aortic valve deformity develops, which may place the child at risk for developing AR progression even after the surgical closure.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, the relatively low risk of cardiopulmonary bypass needs to overcome the benefits of preventing aortic valve complications [3]. There are many reviews about aortic valve complications associated with subarterial VSD, but there are limited data about AR progression after subarterial VSD repair [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Среди основных причин острой АР выделяют повреждения АК в результате травм [27], оперативных вмешательств [28], включая процедуры на клапане, выполненные катетерным способом [29], и осложнений инфекционного эндокардита [30]. Хроническая АР имеет намного больше причин и, кроме инфекционного эндокардита, ревматической болезни сердца [11,31] и системных заболеваний соединительной ткани [32], ответственных также и за поражение МК, развивается при дегенеративных изменениях АК (фиброкальциноз) [33,34], сифилисе [35], спондилоартритах (анкилозирующем спондилите (АСп)) [36], псориатическом [37] и реактивном артритах [38]), васкулитах с поражением артерий крупного калибра (неспецифический аортоартериит [39], гигантоклеточный артериит [40], болезнь Бехчета [41]).…”
Section: этиологияunclassified